Level of Knowledge and Attitude of Blue Lagoon Tourism Managers in The Implementation of The COVID-19 Health Protocol - Subagyono (LPPM Universitas dr. Soebandi, 2023)
Background: There were 2,955 confirmed positive cases of COVID-19 in Ngemplak District in 2021, with 98 deaths. Indonesia is in a transitional stage from the pandemic to the endemic. The policy of easing the use of masks causes a decrease in hand hygiene behaviour and a lack of sanitation facilities increasing the risk factors for transmission of COVID-19 in tourist attractions.Purpose: This study aims to determine the management of knowledge and attitudes towards the Blue Lagoon tourism health in implementing health protocols during the transition from the pandemic to the endemic of COVID-19.Methods: This type of research is analytical descriptive research with a cross-sectional approach. The research instrument used a questionnaire with an accidental sampling technique totalling 30 respondents. Data were analyzed by univariate and bivariate.Results: The results showed that 29 people (93.5%) had good knowledge of the respondents with the protocol implementation with a p-value of 0.853. Respondents' attitudes to the protocol implementation showed a positive category of 28 people (90.3%) with a p-value of 0.790.Conclusions: This study concludes that there is no significant relationship between knowledge and attitudes in implementing of the COVID-19 health protocols.